Psychological dysfunctions in women with bronchial asthma - Natalia G. Astafieva; Denis Yu. Kobzev; Galina N. Strilets; Inna V. Gamova; Irina A. Perfilova; Ekaterina N. Udovichenko (Бюллетень сибирской медицины)
Background. The importance of psychosocial factors in the management of bronchial asthma (BA) is discussed in clinical guidelines, including in international and national clinical guidelines. However, a specific evaluation of their role as a cause of poor asthma control in susceptible patients is required. Aim. Assessment of psychological health of women with different levels of asthma control.Materials and methods. The study included 108 women with asthma observed in Saratov center for Allergology who were stratified into 3 groups according to the control level (good, partial, uncontrolled, according to GINA). In establishing a diagnosis of asthma, standard methods were used (medical history, symptoms, spirography). To assess the level of control, ACQ-5 (Asthma Control Questionnaire 5 items-self-administered) was used, to assess the quality of life, questionnaires AQLQ-S (Asthma Quality of Life Questionnaire S); SF-36 (36-ltem MOS Short-Form Health Survey), a standardized and validated Russian version of the women’s health questionnaire WHQ (Women’s Health Questionnaire) were used; for psychological diagnosis and evaluation of social and personal competencies that contribute to the preservation and improvement of human health (the intellectual, personal, emotional, physical, social, creative, spiritual aspects), integrated multimodal questionnaire was used. The comparison was conducted with a control group of men with bronchial asthma, comparable in age and level of control.Results. Women with poorly controlled asthma had worse performance of AQLQ-S (combined median score of 3,43 instead of 5,13 in the group of good control; p < 0,05); all scales of the SF-36, including the general condition (43,48 against 55,07), role of physical (25,93 against 57,76) and emotional problems (43,83 against 64,37); at p < 0.05. According to the WHQ questionnaire (the inverse relationship: the higher the score, the lower the quality of life) in the group with poor control there is a high level of depression (mean 0,36 versus 0,24; p < 0,05); physical health problems are marked (0,47 against 0,27; p < 0,05). There is a very low selfestimation of their attractiveness in BA (0,71 and 0,64 for bad and good control, respectively). According to the integrated multimodal questionnaire, in both men and women with asthma almost identical results were obtained on the scales sensitive to manifestations of anxiety-depressive symptoms, emotional balance, scales of emotional skills, correlating with severe alexithymia and low capacity for reflection. Among women the proportion of individuals with high scores of intellectual functioning, strong-willed competence, goal-setting, and ability of making contacts was higher.Conclusion. The severity of asthma and disease control are closely linked with the psychological condition of the patient. Psychological dysfunctions are correlated with suboptimal BA control. It is important to understand psychological differences in women and to educate patients in both effective BA control and in establishing individualized asthma management strategies.There is a need for a multidisciplinary approach aimed at the identification and effective correction of asthma. The study of the psychological characteristics of personality and motivational sphere of the patient can help to optimize therapy, improve monitoring and prognosis of the disease.